THE INFLUENCE OF HEALTH EDUCATION ON THE KNOWLEDGE AND ATTITUDE OF PREMENOPAUSE WOMEN - Herlina Memah; Dorce Sisfiani Sarimin; Anggrina Claudia Yubu (Jurnal Ilmiah Perawat Manado (Juiperdo), 2022)
Introduction: Premenopause is a matter that is feared and feared by every woman. Changes that occur during premenopause will cause decreased estrogen hormone production accompanied by psychological and physical complaints, which are characterized by irregular menstrual cycles with prolonged menstrual bleeding and many bleeding sizes accompanied by pain. Along with decreased organ function a woman will experience anxiety which will affect relations with her husband and social environment which results in a woman's self-confidence decreases. Purpose: The purpose of this study was to determine, examine and analyze articles relating to the Effects of Health Education on Knowledge and Attitudes of Premenopausal Mothers. The design used is Literature Review, articles are collected using search engines such as Science Direct, Pubmed, Google Scholar. Criteria for articles used are those published in 2016-2020. Keywords used in article search are health education, knowledge, attitudes, premenopausal women by getting 167 articles or journals and only 8 articles are used that are appropriate, through objective analysis, topic suitability, research methods used, and the results of each article. Results: There are effective results in the implementation of health education about knowledge and attitudes in premenopausal mothers.